METHODOLOGICAL RECOMMENDATIONS FOR TEACHING FOREIGN LANGUAGES TO SCHOOLCHILDREN: 1-SON 3-TO’PLAM IYUL 2023 yil - Jizzakh StatePedagogical University Foreign Languages Faculty, Pardaeva Guzal Ahrorkul qizi (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Through this article, "Methodical recommendations for teaching foreign languages to schoolchildren are discussed